A clinical and histopathological study of malformations observed in fetuses infected by the Zika virus. (5th October 2018) - Beaufrère, Aurélie; Bessières, Bettina; Bonnière, Maryse; Driessen, Marine; Alfano, Christian; Couderc, Thérèse; Thiry, Marc; Thelen, Nicolas; Lecuit, Marc; Attié‐Bitach, Tania; Vekemans, Michel; Ville, Yves; et al.
Abstract: Background: The recent outbreak of Zika virus (ZIKV) infection and the associated increased prevalence of microcephaly in Brazil underline the impact of viral infections on embryo fetal development. The aim of the present study is to provide a detailed clinical and histopathological study of the fetal disruption caused by the ZIKV, with a special focus on the associated neuropathological findings. Methods: A detailed feto‐placental examination, as well as neuropathological and neurobiological studies were performed on three fetuses collected after pregnancy termination between 22 and 25 weeks of gestation (WG), because brain malformations associated with a maternal and fetal ZIKV infection was diagnosed. Results: In all three cases, the maternal infection occurred during the first trimester of pregnancy. A small head was observed on the ultrasound examination of the second trimester of pregnancy and led to the diagnosis of ZIKV fetopathy and pregnancy termination. The fetal histopathological examination was unremarkable on the viscera but showed on the testis an interstitial lymphocytic infiltrate. The placenta contained a Hofbauer cells hyperplasia with signs of inflammation. Neuropathological findings included a meningoencephalitis and an ex va cuo hydrocephalus. Immunohistochemical studies showed the presence of T lymphocytic and histiocytic meningitis associated with an abundant cerebral astroglial and macrophagic reaction. In situ hybridization demonstrated, abundant ZIKV particles within the cerebral parenchyma mainly in the ventricular/subventricular zone and in the cortical plate. In addition massive cells death and endoplasmic reticulum damage were present. Conclusion: The present study reports on the clinical and histopathological findings observed in three fetuses infected by the ZIKV. It emphasizes the severity of brain damages and the minimal visceral and placental changes observed upon ZIKV infection. This confirms the selective neurotropism of ZIKV. Finally, it allows us to describe the cascade of multifactorial developmental defects leading to microcephaly.